2020
DOI: 10.1002/csc2.20275
|View full text |Cite
|
Sign up to set email alerts
|

Identifying inbred lines with resistance to endemic diseases in exotic maize germplasm

Abstract: Mal de Rio Cuarto (MRC) and common rust (CR), caused by Mal de Rio Cuarto virus (MRCV) and Puccinia sorghi, respectively, are endemic diseases affecting maize (Zea mays L.) production in Argentina. Exotic maize germplasm is an important source of resistance to these diseases. The aim of this work was to identify maize lines that exhibit MRC and CR resistance. A multienvironment trial was performed to phenotypically assess a diverse panel of inbred lines from the International Maize and Wheat Improvement Center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Although host genetic background and the environmental conditions may significantly affect the performance of resistance genes, an investigation to determine the clusters of genes present in tropical germplasm highly resistant, resistant or MR to CR should be considered. A few studies have reported QTLs for rust resistance in tropical maize (Danson, Lagat, Kimani, & Kuria, 2008; Rossi et al., 2020; Zheng et al., 2018). Some of the highly resistant lines identified in this study could be good candidates to develop populations for fine mapping some of the large effect QTLs for resistance to CR (Danson et al., 2008; Rossi et al., 2020; Zheng et al., 2018) and potentially for development of breeder‐ready markers for selection in large breeding populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although host genetic background and the environmental conditions may significantly affect the performance of resistance genes, an investigation to determine the clusters of genes present in tropical germplasm highly resistant, resistant or MR to CR should be considered. A few studies have reported QTLs for rust resistance in tropical maize (Danson, Lagat, Kimani, & Kuria, 2008; Rossi et al., 2020; Zheng et al., 2018). Some of the highly resistant lines identified in this study could be good candidates to develop populations for fine mapping some of the large effect QTLs for resistance to CR (Danson et al., 2008; Rossi et al., 2020; Zheng et al., 2018) and potentially for development of breeder‐ready markers for selection in large breeding populations.…”
Section: Discussionmentioning
confidence: 99%
“…Both race specific (Hu & Hulbert, 1996; Hulbert, 1997; Hulbert, Lyons, & Bennetzen, 1991) and partial resistance (Gingera et al., 1994; Randle, Davis, & Groth, 1984) to CR have been reported. Several studies have identified quantitative trait loci (QTL) for resistance to CR on different chromosomes in different germplasm (Brown, Juvik, & Pataky, 2001; Kerns, Dudley, & Rufener, 1999; Lübberstedt et al., 1998; Olukolu, Tracy, Wisser, De Vries, & Balint‐Kurti, 2016; Rossi, Ruiz, Bonamico, & Balzarini, 2020; Zheng et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several recent studies, a broad genetic variation for common resistance was observed in tropical maize, and a few tropical maize inbred lines showing good resistance to common rust were identified (Rossi et al, 2020;Sserumaga et al, 2020). Among 50 tropical adapted maize breeding lines developed by International Maize and Wheat Improvement Center (CIMMYT), 12 lines with broad genetic diversity were identified as the potential donors of resistance alleles, and these lines are valuable breeding materials for the development and deployment of resistant hybrids to control common rust in tropical maize (Sserumaga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Breeding for resistance is the preferred method for controlling common rust, which is the most cost-effective, environment-friendly, and sustainable approach [2]. Rossi et al [3] reported six tropical lines from CIMMYT (International Maize and Wheat Improvement Center) highly resistant to common rust. Sserumaga et al [4] identified 12 common rust resistant lines out of 50 tropical maize inbred lines.…”
Section: Introductionmentioning
confidence: 99%